Effectiveness of natural soil and activated carbon mixture as barrier material in riverbank filtration system - Noor Amira, Luxman (2014)
Water is our body's principal chemical component and makes up nearly 60 percent of our body weight. Most of the water resources come from the river. However, water pollution in Malaysia increase every day. Therefore, river water's quality is an important parameter that must be preserved and monitored. One of the alternative ways to improve the water quality is by using Riverbank Filtration Method (RBF). It is used as an alternative for an efficient and economical drinking-water treatment technology. Riverbank material and its nature soil may not be suitable to treat water until standard water quality achieved, so the alternative design should be considered, by adding artificial barriers to the soil. The main objectives of this study are to determine the effectiveness of nature soil and activated carbon as an artificial barrier in order to get the improvement of water quality for drinking involving natural filtartion. Based on the findings, the mixture of natural soil and activated carbon can be used as filtration media in the riverbank filtration system, but need further treatment because the natural soil of the river itself does not efficient enough to support this system.